Analisis Akuntabilitas dan Transparansi Pengelolaan Dana Komite pada SMA Negeri 9 Sijunjung - Mesi Putri Yenti; Armel Yentifa; Rasyidah Mustika (Akuntansi dan Manajemen, 2018)
This study aims to determine the application of the principles of accountability and transparency in the management of funds in the committee at Sijunjung 9 Public High School. The application of the principles of accountability and transparency can be seen from the stages of planning, stages of implementation, and stages of evaluation and accountability. This research is a qualitative descriptive study. Data collection methods used are interviews, observation, and documentation. Interviews were conducted with the principal, vice principal, committee treasurer, and committee chairman. The results of this study indicate that the application of the principles of accountability and transparency in the management of the committee funds at SMA Negeri 9 Sijunjung has been going well. The principle of transparency can be seen from the openness in the preparation of the School Budget and Action Plan (RKAS). While the principle of accountability is seen from the Accountability Letter (SPJ), the use of committee funds during one school year is given to parents at the committee meeting at the school.